BIOLOGY OF THE CYPRINID, PUNTIUS FILAMENTOSUS (VALENCIENNES) FROM KANHIRAPUZHA RESERVOIR, KERALA - PALANISWAMY, RANI; MANOHARAN, S.; UNNITHAN, USHA (Journal of the Inland Fisheries Society of India, 2021)
The reproduction, food and feeding habits, length–weight relationship and relative condition factor (Kn) of Puntius filamentosus (Valenciennes) from Kanhirapuzha reservoir, Kerala was studied from monthly samples collected during April 2010 to March 2011. The regression model fitted for length-weight relationship was log W = - 5.368 + 3.239 log L, R2 = 0.9538 for male and log W = - 5.715 + 3.4243 log L, R2 = 0.9221 for female and log W= - 5.448 + 3.2987 log L, R2 = 0.9043 for both sex of combined. The average ponderal index (Kn) 0.901 described the idyllic habitat to maintain the health of the fish of this reservoir. As evidenced from gonado - somatic index (GSI), two spawning seasons occur, one a short-spelled but rigorous in May - June and another extended, mild in October - February coinciding with southwest monsoon and northeast monsoon respectively. The relative fecundity varied from 490 (September) to 81444 (June) eggs/g body weight of the fish. Diet composition revealed the dominance (> 85%) of digested plant matter followed by phytoplankton groups.Key words : Length-weight relation, fecundity, feeding habits, Puntius filamentosus, reservoir, India